Manager of the Club of St. Anthony - Mumbai Archive Project (Jio Institute, 2024)
Mr Antonio Barretto is the current manager of the Club of St. Anthony. A member of the club since 1973, he has a longstanding connection to the place. In 2013, he took up residence in the kudd and now manages its day-to-day affairs, keeping it operational.